2010
DOI: 10.1111/j.1752-0606.2009.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Affirmative Training Matter? Assessing CFT Students’ Beliefs About Sexual Orientation and Their Level of Affirmative Training

Abstract: This study examined couple and family therapy (CFT) students' beliefs about sexual orientation, their self-reported competency working with lesbian, gay, and bisexual (LGB) clients, and the level of affirmative training students received in their CFT programs. One hundred and ninety students from accredited CFT programs completed the study. While participants reported feeling only somewhat competent to work with LGB clients and less than half reported receiving any training on affirmative therapy, the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
122
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 20 publications
12
122
1
1
Order By: Relevance
“…Graduates of family therapy training programs have had little training or coursework on sexual orientation (Godfrey, Haddock, Fisher, & Lund, 2006). Research has shown that more than 75% of family therapy graduates have had less than 2 hours of training related to sexually marginalized populations (Malley & Tasker, 1999) and slightly more than 60% of family therapists reported having received no training on affirmative therapy practices and LGB identity development (Rock, Carlson, & McGeorge, 2010). This lack of training on sexual orientation has led family therapists to believe they are only "somewhat" competent in their abilities to work effectively with LGB clients (Rock et al, 2010).…”
Section: Sexual Orientation Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Graduates of family therapy training programs have had little training or coursework on sexual orientation (Godfrey, Haddock, Fisher, & Lund, 2006). Research has shown that more than 75% of family therapy graduates have had less than 2 hours of training related to sexually marginalized populations (Malley & Tasker, 1999) and slightly more than 60% of family therapists reported having received no training on affirmative therapy practices and LGB identity development (Rock, Carlson, & McGeorge, 2010). This lack of training on sexual orientation has led family therapists to believe they are only "somewhat" competent in their abilities to work effectively with LGB clients (Rock et al, 2010).…”
Section: Sexual Orientation Trainingmentioning
confidence: 99%
“…Research has shown that more than 75% of family therapy graduates have had less than 2 hours of training related to sexually marginalized populations (Malley & Tasker, 1999) and slightly more than 60% of family therapists reported having received no training on affirmative therapy practices and LGB identity development (Rock, Carlson, & McGeorge, 2010). This lack of training on sexual orientation has led family therapists to believe they are only "somewhat" competent in their abilities to work effectively with LGB clients (Rock et al, 2010). Yet despite such limited knowledge and training on sexual orientation, 80% of family therapists report working with LGB clients in therapy (Green & Bobele, 1994).…”
Section: Sexual Orientation Trainingmentioning
confidence: 99%
“…A review of the literature indicates that: (a) supervision is often considered one of the most important mediums through which therapy is taught to trainees; (b) LGB issues are not adequately being addressed within supervision; and, (c) there is a dearth of empirical studies that assess the extent to which marriage and family therapy (MFT) faculty and supervisors are attending to LGB issues within clinical training and supervision (Carlson et al, 2012;Rock et al, 2010), and specifically to the ways in which these issues relate to the experiences of LGB supervisees (e.g., Charlés, Thomas, & Thornton, 2005; Hernandez & Rankin, 2008;Long & Serovich, 2003).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Unfortunately, there are few empirical studies that specifically address the experience of LGB supervisees (Burkard et al, 2009). The few that do exist, however, highlight the importance of creatingLGB-affirming environments for LGB supervisees (e.g., Burkard et al, 2009;Lark & Croteau, 1998) and for supervisees working with LGB clients (e.g., Aducci & Baptist, 2011;Bahr, Brish, & Croteau, 2000;Carlson, McGeorge, & Toomey, 2012;Long, 2002;Rock, Carlson, & McGeorge, 2010).Researchers have noted the importance of providing safety and LGB-affirmative environments for LGB trainees and supervisees (e.g., Burkard et al, 2009;Lark & Croteau, 1998). For example, Lark and Croteau's (1998) study of 14 self-identified LGB doctoral students' mentoring relationship with faculty found that when students felt affirmed and safe in their LGB identities within the training environment, they were able to fully engage in their training.…”
mentioning
confidence: 99%
See 1 more Smart Citation